Making Sense of it: Why Democracy (and Feminism) Needs to Go Beyond Binary Citizenship - Vázquez García, Rafael (The Age of Human Rights Journal, 2022)
This text assumes and departs from three basic premises: 1) identities are not born but constructed through repeated performative actions that are in turn informed by existing social constructions of gender; 2) analysing and understanding the ways in which gender is shared and historically constructed can lead to a construction of gender that goes beyond the binary system on which heteronormativity depends; 3) feminism is inherently democratic and entails the consolidation of the very conception of ​​democracy. If feminism wants to remain so, it concludes, it cannot but embrace the theoretical framework and action of non-binary citizenship conceived by Queer Theory.